A tale of two maps: the town plans of Manchester by William Green and Charles Laurent. (2016) - Wyke, Terry; Robson, Brian
Abstract : The two plans of Manchester and Salford by Charles Laurent (1793) and William Green (1794) have attracted considerable controversy. Laurent's plan has widely been believed to be a mere pirated copy of Green's. However, a comparative analysis of the contents of the two shows that there are numerous features of Laurent's plan that cannot have been derived from Green. While Laurent may have made some use of Green's survey data, his own plan contains significant original information. In studying the transformation of Manchester in the crucial years at the end of the eighteenth century, we need to recognise that the two plans should each be seen as an important historical source in its own right.